Element ratios of planktic foraminifera (Globorotalia inflata) from IODP Site 383-U1542 - Nürnberg, Dirk; Gehre, Nadine; Fessler, Sebastian (PANGAEA, 2024)
The realisation of IODP Expedition 383 DYNAPACC to the subantarctic South Pacific closed a critical gap in available sedimentary records from the pelagic Subantarctic Pacific. The sites for the first time sample the formation area of Southern Ocean Intermediate Water (SOIW) and the core region of the Antarctic Circumpolar Current (ACC) in the Pacific sector of the Southern Ocean, both of which play a critical role in the Pleistocene climate evolution. Our studies are based on samples from IODP Site U1542, which is located proximal to the Chilean continental margin in the Subantarctic Zone (SAZ) close to the Drake Passage (54°42.29' S; 75°35.77' W; ~1110 m water depth; 249 m spliced core length). We use a planktonic foraminiferal multi-species isotope/geochemistry approach, combining high-resolution stable isotope (δ18O, δ13C) time series with elemental geochemistry (Mg/Ca). We intend to reconstruct the paleophysical and -chemical characteristics of surface, subsurface, and thermocline watermasses in order to understand their long-term dynamics, their sensitivity to and interaction with changing climate forcing mechanisms throughout the last 780 kyrs, including the major climate transition of the Mid-Brunhes Epoch (MBE).
Keywords: Foraminiferal geochemistry; IODP 383; Sea surface; Site 1542; Southeast Pacific; subsurface